2007
DOI: 10.1108/14720700710727131
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and financing decisions of Ghanaian listed firms

Abstract: Purpose -This paper seeks to examine the relationship between corporate governance and the capital structure decisions of listed firms in Ghana.Design/methodology/approach -Multiple regression analysis is used in the study in estimating the relationship between the corporate governance characteristics and capital structure.Findings -The empirical results show statistically significant and positive associations between capital structure and board size, board composition, and CEO duality. The results generally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
243
5
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(308 citation statements)
references
References 30 publications
44
243
5
16
Order By: Relevance
“…Pfeffer and Salancick (1978) were the first who showed that there is a significant relationship between capital structure and board size. However, Abor (2007) proved that this significant relationship is positive. In contrast, Berger et al (1997) found that corporations which have many members on their board, in general, have low gearing levels.…”
Section: Introduction©mentioning
confidence: 94%
See 1 more Smart Citation
“…Pfeffer and Salancick (1978) were the first who showed that there is a significant relationship between capital structure and board size. However, Abor (2007) proved that this significant relationship is positive. In contrast, Berger et al (1997) found that corporations which have many members on their board, in general, have low gearing levels.…”
Section: Introduction©mentioning
confidence: 94%
“…On the other hand, Pfeffer and Salancick (1978) found that a high proportion of outside directors is associated with high leverage supporting the idea that independent directors help firms to raise more debt through the reduction of information asymmetry, the enhancement of a firm's status and the recognition and exploitation of all available resources. Jensen (1986), Berger et al (1997) and Abor (2007) also found a positive relationship between debt levels and outside directors.…”
Section: Introduction©mentioning
confidence: 99%
“…With respect to the African setting, a number of studies have analysed the impact of CG structures on a number of issues, such as financing decisions of firms (KyereboahColeman and Biekpe, 2006a;Abor, 2007;Abor and Biekpe, 2007), incidences of listing suspensions (Mangena and Chamisa, 2008) and dividend performance (Bokpin, 2011). A limited number of studies have also investigated the effects of different CG mechanisms, such as the frequency of board meetings (El Mehdi, 2007;Ntim and Osei, 2011), ownership structure (Mangena and Tauringana, 2008;Sand et al, 2010), board size (Ho and Williams, 2003;Kyereboah-Coleman et al, 2006) and board composition (Kyereboah-Coleman and Biekpe, 2006b;Sunday, 2008) on corporate performance with equally inconclusive results.…”
Section: Introductionmentioning
confidence: 99%
“…From corporate governance perspective, as depicted in Tabled 7, solely Board Size has a weak positive significance on leverage consistent with Lu et al (2012), Abor (2007) and Sheikh and Wang (2012). The findings above hold when the dependent variable is taken as long-term leverage.…”
Section: Results Of Panel Data Regressionsmentioning
confidence: 67%